Effects of micro-oxygenation on the aroma of Cabernet Sauvignon wine from Ningxia, China - Zhang, Zhong; Zhang, Qingchen; Wang, Huiqing; Xia, Hongchuan; Sun, Lijun; Zhang, Junxiang (International Journal of Agricultural and Biological Engineering, 2022)
Micro-oxygenation (MOX) is an effective post-harvest technique for the flavor improvement of grape wine. This study investigated the effect of MOX on the aroma quality of Ningxia wine for the first time. Three sub-region Cabernet Sauvignon dry red wines were treated with different levels of oxygen before or after malolactic fermentation. The wine aroma was analyzed through gas chromatography-mass spectrometry (GC-MS) and quantitative descriptive analysis (QDA) after six months of aging. The data obtained demonstrated that the dose and timing of oxygen addition were both key factors influencing the effectiveness of MOX. The most noticeable modifications in wine aroma compounds were generated by an oxygen dosage of 30 mL·month/L added before malolactic fermentation. Predominantly, the concentrations of 2-phenylethanol, benzaldehyde, diacetyl, and 2,3-pentanedione showed an increased pattern upon MOX treatments. The sensory analysis revealed that MOX improved the aroma quality of wine by decreasing green and animal odors, meanwhile enhancing the olfactory intensities of dried fruits, flowers, and nuts. This work confirmed that MOX was suitable for aroma modification of Cabernet Sauvignon dry red wine from Ningxia and established a preliminary MOX procedure that can serve as a reference for future applications. Keywords: grape wine, micro-oxygenation, volatile organic compounds, aroma profiles, Ningxia DOI: 10.25165/j.ijabe.20221504.7158 Citation: Zhang Z, Zhang Q C, Wang H Q, Xia H C, Sun L J, Zhang J X. Effects of micro-oxygenation on the aroma of Cabernet Sauvignon wine from Ningxia, China. Int J Agric & Biol Eng, 2022; 15(4): 251–263.